Football player's performance and market value - He, M.; Cachucho, R.; Knobbe, A. (Machine Learning and Data Mining for Sports Analytics ECML/PKDD 2015 workshop, 2015)
A lot of money is involved with the transfers of top players in the big European football leagues. For various reasons, obtaining a good economic valuation of football players throughout the year is valuable, in other words, not just when a player has just transferred. Furthermore, it is relevant to consider how the market value of a player relates to the performance of that player. Both these factors again depend on the various parameters of the player, that might be gleaned from various public sources on the web. In this paper, we demonstrate how market value and performance of La Liga (the Spanish League) players can be modeled using extensive public data sources.